The in vivo study of cardiac mechano-electric and mechano-mechanical coupling during heart development in zebrafish - Baillie, Jonathan S.; Gendernalik, Alex; Garrity, Deborah M.; Bark, David; Quinn, T. Alexander (Frontiers in Physiology, 2023)
In the adult heart, acute adaptation of electrical and mechanical activity to changes in mechanical load occurs via feedback processes known as “mechano-electric coupling” and “mechano-mechanical coupling.” Whether this occurs during cardiac development is ill-defined, as acutely altering the heart’s mechanical load while measuring functional responses in traditional experimental models is difficult, as embryogenesis occurs in utero, making the heart inaccessible. These limitations can be overcome with zebrafish, as larvae develop in a dish and are nearly transparent, allowing for in vivo manipulation and measurement of cardiac structure and function. Here we present a novel approach for the in vivo study of mechano-electric and mechano-mechanical coupling in the developing zebrafish heart. This innovative methodology involves acute in vivo atrial dilation (i.e., increased atrial preload) in larval zebrafish by injection of a controlled volume into the venous circulation immediately upstream of the heart, combined with optical measurement of the acute electrical (change in heart rate) and mechanical (change in stroke area) response. In proof-of-concept experiments, we applied our new method to 48 h post-fertilisation zebrafish, which revealed differences between the electrical and mechanical response to atrial dilation. In response to an acute increase in atrial preload there is a large increase in atrial stroke area but no change in heart rate, demonstrating that in contrast to the fully developed heart, during early cardiac development mechano-mechanical coupling alone drives the adaptive increase in atrial output. Overall, in this methodological paper we present our new experimental approach for the study of mechano-electric and mechano-mechanical coupling during cardiac development and demonstrate its potential for understanding the essential adaptation of heart function to acute changes in mechanical load.